Familial amyloidotic polyneuropathy in Sweden: a pedigree analysis. Issue 5 (May 1993) - Drugge, U; Andersson, R; Chizari, F; Danielsson, M; Holmgren, G; Sandgren, O; Sousa, A
Abstract : Extended genealogical studies were performed on the heredity patterns in Swedish patients with familial amyloidotic polyneuropathy (FAP) using Swedish historical archives. The population studied included 239 patients: 109 patients were linked to five large pedigrees and 80 patients belonged to 30 smaller pedigrees or nuclear families. In the remaining 50 cases, no genealogical links were found. Differences in mean ages of onset between the different pedigrees were found, although a considerable variation within the pedigrees was also present. There was a tendency for later ages of onset among older generations than younger ones: descendants of affected mothers seem to be more prone to anticipation in age of onset than descendants of affected fathers. Furthermore, there seems to be a tendency for earlier ages of onset among patients with a carrier mother than a carrier father. Some extended pedigrees, from the Skellefteå and Piteå areas, are presented in detail. The former go back into the middle of the 17th century. One important conclusion is that the mutational event may have occurred in late mediaeval times.